Neutron-Multiplicity Measurement in Muon Capture on Oxygen Nuclei in the Gadolinium-Loaded Super-Kamiokande Detector. - Miki,S; Abe,K; Abe,S; Asaoka,Y; Bronner,C; Harada,M; Hayato,Y; Hiraide,K; Hosokawa,K; Ieki,K; Ikeda,M; Kameda,J; et al. (Phys Rev Lett, 2026)
In recent neutrino detectors, neutrons produced in neutrino reactions play an important role. Muon capture on oxygen nuclei is one of the processes that produce neutrons in water Cherenkov detectors. We measured neutron multiplicity in the process using cosmic ray muons that stop in the gadolinium-loaded Super-Kamiokande detector. For this measurement, neutron detection efficiency is obtained with the muon capture events followed by gamma rays to be 50.2_{-2.1}^{+2.0}%. By fitting the observed multiplicity considering the detection efficiency, we measure neutron multiplicity in muon capture as P(0)=24±3%, P(1)=70_{-2}^{+3}%, P(2)=6.1±0.5%, P(3)=0.38±0.09%. This is the first measurement of the multiplicity of neutrons associated with muon capture on oxygen without neutron energy threshold.